PS-061 The recognition/reconciliation process in elderly patients: a retrospective study in geriatric and internal medicine wards. (24th March 2015) - Chiarelli, M; Antoniazzi, S; Venturini, F; Ladisa, V; Lodi, M; Nobili, A; Pasina, L; Porzio, M; Santalucia, P; Mannucci, P
Abstract : Background: Polypharmacy, common in the elderly, is an important risk factor for drug-related problems. In this context, the hospital pharmacist can contribute to supporting clinicians in promoting the safe use of medicines. Purpose: To identify the need for an appropriate medicines reconciliation system in a sample of hospitalised elderly patients. Material and methods: Medical records of patients ≥65 years taking ≥5 drugs admitted during a one-month period to 5 general medicine and geriatric wards were retrospectively reviewed. The following data were collected by a hospital pharmacist: number of drugs prescribed, dose omission, frequency, administration route, pharmaceutical form and potential drug-drug interactions. Results: We analysed the medical records of 75 patients (36 men, 39 women, mean age 81 years). Overall, patients were admitted with 634 drugs used at home; in the first 24 h after admission and at discharge, 723 and 645 drugs were prescribed, respectively. At the recognition stage, the dosage form was omitted in 17% of prescriptions, the dose in 12%, route of administration in 20%, frequency in 26%. At discharge rates of omission decreased to 2% for dosage form, 2% for route of administration, 7% frequency. Overall, 816 potential drug-drug interactions were identified. In 13 medical records medicines were not prescribed in accordance with the hospital formulary; allergies/intolerances were not taken into account in 2 discharge letters and in 2 inpatient prescriptions, while 9 suspected adverse drug reactions were not notified. Conclusion: The review of the actual process of accuracy of drug recording in the patient's medical record highlights the need for a more structured procedure. An active role for hospital pharmacists is foreseen, in order to ensure the safe use of medicines. References and/or acknowledgements: No conflict of interest.